Two new species of Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the Seribuat Archipelago, Pahang and Johor States, West Malaysia - Das, Indraneil; Grisme, Larry Lee (The Herpetologists' League, 2003)
Two new species of Cnemaspis Strauch, 1887 are described from Pulau Tioman and Pulau Aur in the Seribuat Archipelago, Pahang and Johor States, respectively, off the southeast coast of West Malaysia. The Pulau Tioman species was previously allocated to C. nigridia by earlier workers, but is distinguishable from all other species on the basis of squamation, color pattern, and maximum size attained. The second new species from Pulau Aur is the first record of Cnemaspis from that island and is similarly distinguished from all other species on the basis of squamation and color pattern.